On the key factors of usability in small-sized mobile touch-screen application - Gündüz, Feyza; Pathan, Al-Sakib Khan (Science & Engineering Research Support soCiety (SERSC), 2013)

(untitled)
The purpose of this work is to present a practical study on the key factors of usability in small-sized mobile touch-screen applications. Though using smart phones has brought great easiness in our daily life in many ways, many smart phone applications often remain underutilized due to the poor consideration of end-users in the development phase, thus decreasing potential profit of companies. In this paper, we investigate usability problems for a mobile flight booking application on touch-screen phones, and suggest practical solutions. The application is a critical one that can represent the cases of a wide number of smart phone applications. Main expectations of users are presented from HCI (Human Computer Interaction) perspective and discussed through the case study. Questionnaire and interview methods were used for collecting data. Prototype has also been utilized to verify users' expectations of mobile flight booking more accurately. The interviewees who were in the range of ages 18-40 have been randomly selected for this study, which could be also considered as a realistic set because of their diversity. Results have revealed that users are very much concerned about the easiness and the lucidness of functions. Usability is a highly considerable subject for users to prefer a mobile flight booking application over booking tickets via online or agencies.